2016
DOI: 10.3390/e18040100
|View full text |Cite
|
Sign up to set email alerts
|

Chaos on the Vallis Model for El Niño with Fractional Operators

Abstract: Abstract:The Vallis model for El Niño is an important model describing a very interesting physical problem. The aim of this paper is to investigate and compare the models using both integer and non-integer order derivatives. We first studied the model with the local derivative by presenting for the first time the exact solution for equilibrium points, and then we presented the exact solutions with the numerical simulations. We further examined the model within the scope of fractional order derivatives. The fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Only a couple of papers have appeared recently. Alkahtani et al [10] have studied Vallis model with local derivatives, Caputo derivatives and Caputo-Fabrizio derivative. They have also drawn phase portraits for commensurate fractional Vallis system with Caputo derivative for p = 0.3 and α = 0.85, 0.55, 0.25.…”
Section: Introductionmentioning
confidence: 99%
“…Only a couple of papers have appeared recently. Alkahtani et al [10] have studied Vallis model with local derivatives, Caputo derivatives and Caputo-Fabrizio derivative. They have also drawn phase portraits for commensurate fractional Vallis system with Caputo derivative for p = 0.3 and α = 0.85, 0.55, 0.25.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fractional calculus has received much attention due to fractional derivatives providing more accurate models than their integer-order counterparts. Many examples have been found in different interdisciplinary fields [25], ranging from the description of viscoelastic anomalous diffusion in complex liquids, D-decomposition technique for control problems, chaotic systems; to macroeconomic models with dynamic memory, forecast of the trend of complex systems, and so on [26][27][28][29][30][31][32][33][34]. Those works have demonstrated that fractional derivatives provide an excellent approach to describing the memory and hereditary properties of real physical phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, it has been shown that fractional-order dynamics can be observed for instance in viscoelastic systems, in dielectric polarization, in electromagnetic waves, just to name some [3]- [5]. Meanwhile another prolific field of science, namely chaos theory, has acquired a new development to address the challenging problem of chaos synchronization due to its potential applications in physics, chemistry, telecommunication, biology, medicine and so on [6]- [18]. The streaming of research within this area aims at achieving master-slave synchronization between two chaotic systems by choosing various kinds of methods to extend and enrich the pioneering work of Pecora and Carroll [19].…”
Section: Introductionmentioning
confidence: 99%